Sistem Rekomendasi Pemilihan Laptop Menggunakan Metode Content-Based Filtering Berbasis Spesifikasi Produk - Pratiwi, Niken; Hartanti, Dwi; Arum Sari, Aprilisa (Infotek: Jurnal Informatika dan Teknologi, 2025)
The advancement of information technology has led to an increasing demand for computing devices, particularly laptops. The wide variety of options based on specifications, brands, and prices often makes it difficult for consumers to choose the device that best suits their needs. Therefore, this study aims to design a laptop recommendation system using the Content-Based Filtering (CBF) approach to provide relevant suggestions based on user preferences. The developed system applies Term Frequency-Inverse Document Frequency (TF-IDF) and Cosine Similarity methods to measure the similarity between key laptop features such as processor type, RAM capacity, storage, and graphics card. Laptop data was obtained through a web scraping process from trusted e-commerce websites and integrated into a web-based platform. Testing results show that the system can automatically generate personalized and highly relevant recommendations. The main contribution of this study is the development of an efficient content-based laptop recommendation system utilizing a combination of TF-IDF and Cosine Similarity techniques. In addition to facilitating faster decision-making in selecting a laptop, the system also demonstrates the practical application of machine learning-based recommendation technologies in the e-commerce sector. This research further provides a foundation for developing similar recommendation systems in other contexts that require content-based personalization approaches.